HOW TO PREVENT FRAUD? (CASE STUDY ON PT. ALFARIA TRIJAYA) - Ibnu Rachman; Wien Dyahrini (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this study is to find out the effect of internal auditing on fraud prevention by internal control as a moderating variable on PT. Alfaria Trijaya. The research method used in this research is the exoplanet research method. The population in this research is corporate audit finance division and operation division PT Alfaria Trijaya. Data collection techniques used in this study are using questionnaires. While the analysis method used in this study is regression moderation analysis at a significance level of 5%. Programs used in analyzing data using SPSS Ver. 23.0. The results show that internal auditing, fraud prevention, and internal control at PT. Alfaria Trijaya. belongs to the excellent category. In addition, the results of partial and simultaneous research showed that the Internal auditing on Fraud Prevention (Fraud) had a significant effect by moderating internal control in PT. Alfaria Trijaya. That is, internal control can moderate that is strengthening the relationship.